Aesthetics of expression in contemporary Sudan sculpture - Hamzah, Maha Saleh; Alkilabi, Mahmood Ajmi Jasim (International Journal of Psychosocial Rehabilitation, 2020)
In connection with international art, Sudanese art has, since the fifties of the twentieth century, tended towards expressive thought using material, technology, and coming up with material and technical combinations that emphasize the creative aspect of contemporary Sudanese art. Therefore, this study came with the aim of revealing the aesthetics of expression in the works of contemporary Sudanese sculptors and to identify expressive and aesthetic values and stating the stylistic characteristics of it, this study is based on four chapters: The general framework of the research. As for the theoretical framework, it included three topics, the first was entitled Beauty in Human Thought, and the second was entitled Expression. The third topic was the development of plastic arts in Sudan. The researcher concluded with the indicators that resulted from the theoretical framework.As for the research procedures, in which the researcher defined his research community with (20) sculptural works, from which the researcher intentionally chose his research samples, which were determined by(3) sculptural works. Adopting the descriptive analytical method in its analysis, and sealing with the analysis of samples.The sculpture concluded with the results, the most important of which are: • The research showed that the material is no longer just a physical medium that carries the shape in contemporary Sudanese sculpture, but rather it became aesthetic to dealing with it, through its sensory and synthetic properties, which the artist revealed through technical synthesis.• The relations and connections in the Sudanese sculpture art were limited to the technical methods of processing, and the features of the Sudanese sculpture remained conservative and linked to the historical legacy and its historical culture.